Noninvasive Facial Rejuvenation. Part 2: Physician-Directed—Neuromodulators and Fillers - Dickey, Ryan M.; Louis, Matthew R.; Cox, Joshua A.; Mohan, Kriti; Lee, Edward I.; Nigro, Marjory G. (Seminars in Plastic Surgery, 2016)
A proper knowledge of noninvasive facial rejuvenation is integral to the practice of a cosmetic surgeon. Noninvasive facial rejuvenation can be divided into patient- versus physician-directed modalities. Patient-directed facial rejuvenation combines the use of facial products such as sunscreen, moisturizers, retinoids, α-hydroxy acids, and various antioxidants to both maintain youthful skin as well as rejuvenate damaged skin. Physicians may recommend and often prescribe certain products, but patients are in control with this type of facial rejuvenation. On the other hand, physician-directed facial rejuvenation entails modalities that require direct physician involvement, such as neuromodulators, filler injections, laser resurfacing, microdermabrasion, and chemical peels. With the successful integration of each of these modalities, a complete facial regimen can be established and patient satisfaction can be maximized. This article is the second in a three-part series describing noninvasive facial rejuvenation. Here the authors discuss neuromodulators and fillers in detail, focusing on indications for use, techniques, and common side effects.
Keywords: neuromodulators; fillers; noninvasive facial rejuvenation